Power conversion and control of wind energy systems - Wu, Bin Lang, Yongqiang Zargari, Navid Kouro, Samir (Wiley, IEEE, 2011)
The book covers a wide range of topics on wind energy conversion and control from the electrical engineering aspect. It includes wind generators and modeling, power converters and modulation schemes, operating principle of fixed and variable speed wind turbines, advanced generator control schemes, active and reactive power controls of individual wind and is a valuable reference book for academic researchers, practicing engineers, and other professionals. The book can also be used as a textbook for graduate level and final year undergraduate-level courses